Implementing Computer Vision for Tracking and Monitoring Rehabilitation Progress in Patients with Orthopedic Injuries - Assudani, Purshottam J.; Dolly, Bably; M. Arun, M. Arun; Chakravarthy R, Arun; Kumar, Jitendra; E Sreedevi, E Sreedevi (Journal of Neonatal Surgery, 2025)
Regular monitoring and Tracking are essential in orthopedic rehabilitation to ensure the effective recovery of patients. Traditional rehabilitation assessments are limited to manual qualitative observations and marker-based motion tracking which are costly and are invasive/impractical and less scalable. Last Updated on 23 October 2023 by ortech in this research, we investigate the use of computer vision-based tracking systems for tracking rehabilitation progress in orthopedic patients. The study at hand uses markerless motion capture, AI-assisted kinematic and kinetic analysis, remote real time monitoring to improve precision and availability of rehabilitation processes. This approach allows for automated, data-driven evaluations of joint motion and gait patterns by incorporating machine learning algorithms, augmented reality-based rehabilitation, and wearable IMU sensors. This system will not only enhance patient participation but also decrease overload in clinics and offer affordable and real-time rehabilitation solutions. Anticipating this environment in cloud-based fediverse frameworks, and the autonomy-supportive AI interventions that ensue, guarantees compliant and rehabilitative procedural outcomes. This study provides evidence for the feasibility of using computer vision-based approaches for personalized rehabilitation tracking in a non-intrusive, cost-effective and high security manner thus showing promise for improving orthopedic rehabilitation programs in an inpatient and outpatient setting.